The consuming instinct : what juicy burgers, Ferraris, pornography, and gift giving reveal about human nature - Saad, Gad (Prometheus Books, 2011)
What do all successful fast-food restaurants have in common? Why do men's testosterone levels rise when they drive a Ferrari or a Porsche? Why are women more likely to become compulsive shoppers and men more likely to become addicted to pornography? How does the fashion industry play on our innate need to belong? The answer to all of these questions is "the consuming instinct," the underlying evolutionary basis for most of our consumer behavior. In this book, the author, founder of the new field of evolutionary consumption, illuminates the relevance of our biological heritage to our daily lives as consumers.